Wave action on oil rig cylinder members (extreme run-up of waves interacting with an array of columns) - Lu, Jonathan Si'en. (2009)
When designing deep water offshore platform, engineers require an understanding of wave-structure interaction phenomena. In the case of an offshore fixed platform oil rig, the wave run-up on the vertical legs and the amplification of the waves beneath the deck may produce substantial damages to the underside of the lower deck of the structure’s platform. We would term such wave occurrences as extreme run-up in this study. This is often due to deep sea conditions where there are steep short waves. We have focused our review of previous studies on the mechanics of wave uprush of extreme heights and earlier findings on wave interaction with singular and arrayed cylinders. An idea on relevant relationships was understood and their studies also formed the basis of the selection of our parameters and helped us form an independent study on run-ups and arrayed cylinders.